Development of a picture instrument to measure the experiential background of pre-reading children - Schmidt, Carol (My University, 1978)
It was the purpose of this study, (1) to define reading readiness as it relates to a child's life experiences, or his experiential background; (2) to review the literature concerning the readiness factors that influence a child's learning to read, and to review several picture instruments which would test the experiential background of the pre-reading child; and (4) to analyze the results, discuss the educational implications, and give recommendations for future study. Reading readiness must include the child's complete background for learning in terms of his maturation and experience. The child's background for learning or his experiential background is his knowledge of common objects gained through direct concrete experiences. A review was made of existing picture instruments. The SRA Test in Reading, the Peabody Picture Vocabulary Test, and the Pre-Reading Skills Program were examined. None of these instruments were found to have adequate picture material or to measure experiential background. The researcher then gathered colorful photographs for the construction of a picture instrument to measure experiential, background of the learner. The research instrument was given in the spring and summer of 1978 to 39 pre-readers. The Peabody Picture Vocabulary Test was also given for comparative purposes. A comparison of the means of the raw scores of the two instruments yielded a difference of only five. The research instrument was considered to be an appropriate test for the present research population. Additional research should be done in the future to further explore the learner's experiential background.
Keywords: Reading readiness -- Testing.